2022
DOI: 10.3390/life12020183
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Disease and Metabolism

Abstract: Retinal diseases, such as diabetic retinopathy (DR), age-related macular degeneration (AMD), and retinopathy of prematurity (ROP), are some of the leading causes of blindness all over the world [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…With different settings, all models reach a high accuracy of over 91%, supporting our method's effectiveness for robustness. Firstly, for patch size, we select different pairs of patch sizes including (1,4), (2,4), and (1,8), and the results showed that (1,4) achieved the best average performance. K represents how many most similar patches in the feature space each patch needs to select for information aggregation.…”
Section: Ablation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With different settings, all models reach a high accuracy of over 91%, supporting our method's effectiveness for robustness. Firstly, for patch size, we select different pairs of patch sizes including (1,4), (2,4), and (1,8), and the results showed that (1,4) achieved the best average performance. K represents how many most similar patches in the feature space each patch needs to select for information aggregation.…”
Section: Ablation Studiesmentioning
confidence: 99%
“…Retinal diseases, such as diabetic retinopathy (DR), agerelated macular degeneration (AMD), and retinopathy of prematurity (ROP), are some of the leading causes of blindness worldwide [1]. Regular retinal examinations can facilitate early disease diagnosis before the manifestation of any symptomatic indications.…”
Section: Introductionmentioning
confidence: 99%
“…By 2050, there are expected to be approximately 90% more people with vision impairment and 50% more blind people [1]. Retinopathy, as one of the leading diseases causing visual impairment and blindness, includes diabetic retinopathy (DR), age-related macular degeneration (AMD), and many other retinal diseases [2,3]. It has become a national and even an international issue with unmet strategies and treatments.…”
Section: Introductionmentioning
confidence: 99%